2021
DOI: 10.1123/jpah.2020-0761
|View full text |Cite
|
Sign up to set email alerts
|

Regular Voluntary Running Inhibits Androgen-Independent Prostate Cancer Growth in Mice

Abstract: Introduction: Benefits of regular physical exercise were demonstrated as preventive and coadjuvant nonpharmacological anticancer therapy. However, the role of exercise in modulating prostate cancer behavior has yet to be established. Methods: Prostate tumors were induced in C57BL/6 male mice (n = 28) by subcutaneous inoculation of a suspension of murine androgen-independent RM1 cells (1.5 × 105 cells/500 μL phosphate-buffered saline) in the dorsal region. Mice were randomly allocated into 2 study groups: seden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Following a 6-week induction duration, the dorsal regions of the mice were subjected to ocular inspection to identify symptoms resembling skin cancer. The dorsal area of the animal was chosen since it provides more surface area and least disturbed from animal movements ( Esteves et al, 2021 ). Additionally, histological confirmation was performed to validate the presence of these symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Following a 6-week induction duration, the dorsal regions of the mice were subjected to ocular inspection to identify symptoms resembling skin cancer. The dorsal area of the animal was chosen since it provides more surface area and least disturbed from animal movements ( Esteves et al, 2021 ). Additionally, histological confirmation was performed to validate the presence of these symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, acute exercise has been shown to increase ceramide content in skeletal muscle after acute exercise in healthy adult men [ 18 ]. Furthermore, exercise has been shown to increase apoptosis in tumor cells [ 19 , 20 , 21 ]. Together, the demonstration that exercise can increase ceramide in some tissues, and promote apoptosis in tumors, raises the possibility that exercise increases ceramide accumulation in tumor cells to promote cell death and enhance the response to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, preliminary evidence showed that regular physical exercise after a cancer diagnosis decreased the risk of recurrence and mortality and should be considered an important co-adjuvant anticancer therapy [21]. Additionally, it was shown in murine models that the regular practice of physical exercise resulted not only in the inhibition of tumor growth but also in increased life span [22,23]. A recent meta-analysis of pre-clinical studies suggested that although regular physical exercise impacts tumor size, the underlying mechanisms are complex and multifactorial [22].…”
Section: Introductionmentioning
confidence: 99%